Dampak Pembelajaran Berbasis Masalah terhadap Kemampuan Pemecahan Masalah, Koneksi Matematis dan Kecerdasan Emosional Siswa SMP - Armiati, Armiati; Anggraini, Novita; Devi, Sri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Problem solving ability is a skill that each student must have in mathematics learning. But the fact is, there were many students who are constrained when faced to solving mathematic problem. This situation happens due to the studentâs habit to imitate the teacherâs answer that is given during the learning. When the student is given a different kind of problem, they were confused and not able to finish it. This papers discuss the results of problem-based learning to the problem-solving ability for the junior high school student. The study begins by designing problem-based learning devices, followed by applying of the device in learning process, then examined the impact on the problem solving ability of the junior high school student. The results showed that problem-based learning have a positive impact on the problem solving ability of junior high school student.